Modelling and simulation of zero-gravity distillation units with metal foams - Wende, Marc; Staggenborg, Christoph; Kenig, Eugeny Y. (Chemical Engineering Science)
Keywords: Applied Mathematics; Industrial and Manufacturing Engineering; General Chemical Engineering; General Chemistry

Modelling film and rivulet flows on microstructured surfaces using CFD methods - Bertling, René; Hack, M.; Ausner, I.; Horschitz, B.; Bernemann, Sören Antonius; Kenig, Eugeny (Chemical Engineering Science)
Keywords: Applied Mathematics; Industrial and Manufacturing Engineering; General Chemical Engineering; General Chemistry

Modelling film and rivulet flows on microstructured surfaces using CFD methods - Bertling, R.; Hack, M.; Ausner, I.; Horschitz, B.; Bernemann, S.; Kenig, E.Y. (Chemical Engineering Science)
Keywords: Applied Mathematics; Industrial and Manufacturing Engineering; General Chemical Engineering; General Chemistry

Operating window and flexibility of a lab-scale methanation plant - Herrmann, Felix; Grünewald, Marcus; Meijer, Tobias; Gardemann, Ulrich; Feierabend, Lukas; Riese, Julia (Chemical Engineering Science)
Keywords: Applied Mathematics; Industrial and Manufacturing Engineering; General Chemical Engineering; General Chemistry

A PLIC-based method for species mass transfer at free fluid interfaces - Schulz, Andreas; Wecker, Christian; Inguva, Venkatesh; Lopatin, Alexey S.; Kenig, Eugeny Y. (Chemical Engineering Science)
Keywords: Applied Mathematics; Industrial and Manufacturing Engineering; General Chemical Engineering; General Chemistry

Model based random packing optimisation for absorption processes using the hydrodynamic analogy concept - Salten, Alexander Heinrich Johannes; Kenig, Eugeny (Chemical Engineering Science)

Flexibility analysis for demand-side management in large-scale chemical processes: An ethylene oxide production case study - Bruns, Bastian; Di Pretoro, Alessandro; Grünewald, Marcus; Riese, Julia (Chemical Engineering Science)
Keywords: Applied Mathematics; Industrial and Manufacturing Engineering; General Chemical Engineering; General Chemistry

Numerical investigation of liquid flow morphology in structured packings - Olenberg, Alexander; Kenig, Eugeny (Chemical Engineering Science)

A new hydrodynamic analogy model for the determination of transport phenomena in random packings - Salten, Alexander Heinrich Johannes; Maćkowiak, Jan F.; Maćkowiak, Jerzy K.; Kenig, Eugeny (Chemical Engineering Science)

A comparative study of different amine-based solvents for CO2-capture using the rate-based approach - Hüser, Nicole; Schmitz, Oliver; Kenig, Eugeny (Chemical Engineering Science)

Interfacial energy estimation in a precipitation reaction using the flatness based control of the moment trajectories - Vassilev, Vassil; Gröschel, Michael; Schmid, Hans-Joachim; Peukert, Wolfgang; Leugering, Günter (Chemical Engineering Science)
In this paper, we consider a model for precipitation experiments based on the population balance equation. The study revealed a high sensitivity of the system with respect to the modeling of intrinsic parameters, motivating a comprehensive validation of the estimates. In the forward simulation the impact of the influencing parameters including surface energy, nucleus size and distribution is investigated. Subsequently we construct a simplified model of the precipitation process in such a way that it is orbitally flat in terms of control theory, which enables the inverse calculation of the parameters. The numerical results of the inverse simulation for the interfacial energy have been compared to a physical model. The possibility of solving the inverse problem provides a promising way of estimating hardly measurable quantities for more complex molecules.

Modelling titania formation at typical industrial process conditions: effect of surface shielding and surface energy on relevant growth mechanisms - Artelt, C.; Schmid, Hans-Joachim; Peukert, W. (Chemical Engineering Science)
This work investigates the effects of reduced accessible surface area of aggregate particles and of surface energy on relevant particle formation and growth mechanisms during titania formation from the vapour phase at industrial process conditions. Growth due to surface reaction and due to condensation is related to the fraction of the surface area that is exposed to the collision with single molecules. Surface shielding is found to hamper surface reaction and condensation once fractal aggregates start to form. It leads to significantly retarded precursor consumption and produces aggregate particles, which consist of more, but smaller primary particles. Surface energy data are varied within a range as proposed by available literature data. Moderate and high surface energy values result in a thermodynamic barrier to the formation of new particles and are shown to reduce the formation of seed particles by several orders of magnitude. This leads to the formation of aggregate particles which consist of a rather small number of primary particles and mainly grow by surface reaction. The primary contribution of condensation to growth of individual primary particles is shown to be very little. However, condensation should not be neglected as it has a strong impact on particle formation rates and hence on product characteristics such as the number of primary particles and primary particle size.

Predictive simulation of nanoparticle precipitation based on the population balance equation - Schwarzer, Hans-Christoph; Schwertfirm, Florian; Manhart, Michael; Schmid, Hans-Joachim; Peukert, Wolfgang (Chemical Engineering Science)
Nanoparticle precipitation is an interesting process to generate particles with tailored properties. In this study we investigate the impact of various process steps such as solid formation, mixing and agglomeration on the resulting particle size distribution (PSD) as representative property using barium sulfate as exemplary material. Besides the experimental investigation, process simulations were carried out by solving the full 1D population balance equation coupled to a model describing the micromixing kinetics based on a finite-element Galerkin h-p-method. This combination of population balance and micromixing model was applied successfully to predict the influence of mixing on mean sizes (good quantitative agreement between experimental data and simulation results are obtained) and gain insights into nanoparticle precipitation: The interfacial energy was identified to be a critical parameter in predicting the particle size, poor mixing results in larger particles and the impact of agglomeration was found to increase with supersaturation due to larger particle numbers. Shear-induced agglomeration was found to be controllable through the residence time in turbulent regions and the intensity of turbulence, necessary for intense mixing but undesired due to agglomeration. By this approach, however, the distribution width is underestimated which is attributed to the large spectrum of mixing histories of fluid elements on their way through the mixer. Therefore, an improved computational fluid dynamics-based approach using direct numerical simulation with a Lagrangian particle tracking strategy is applied in combination with the coupled population balance–micromixing approach. We found that the full DNS-approach, coupled to the population balance and micromixing model is capable of predicting not only the mean sizes but the full PSD in nanoparticle precipitation.

Evolution of the fractal dimension for simultaneous coagulation and sintering - Schmid, Hans-Joachim; Al-Zaitone, Belal; Artelt, Christian; Peukert, Wolfgang (Chemical Engineering Science)
Simulation results on the evolution of aggregate structure in aerosol processes with coagulation and sintering as the dominant mechanisms are presented. A model for simulation of the three-dimensional morphology of nano-structured aggregates formed by concurrent coagulation and sintering is applied. The model is based on a stochastic diffusion controlled cluster–cluster aggregation algorithm and sintering is modeled as a successive overlapping of spherical primary particles, which are allowed to grow in order to maintain mass conservation. This leads to computer simulated structured aggregates which are then subject to evaluation. Two different methods to determine the fractal dimension are presented which give comparable results. It is shown that even very small particles show the same fractal behavior. Furthermore, equilibrium structures assuming a constant ratio of the characteristic collision time to the characteristic fusion time are considered as well as the kinetics of structural changes due to a change in the ambient conditions.